2017
DOI: 10.1128/genomea.00611-17
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of Klebsiella michiganensis 3T412C, Harboring an Arsenic Resistance Genomic Island, Isolated from Mine Tailings in Peru

Abstract: An arsenic resistance genomic island in the bacterium Klebsiella michiganensis 3T412C was isolated from mine tailings from Peru. This genomic island confers adaptation to extreme environments with high concentrations of arsenic. Isolate 3T412C contained a complete set of genes involved in resistance to arsenic. This operon is surrounded by putative genes for resistance to other heavy metals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…and P. vagans associated with S. aurata (excluding cases where these bacteria are used as probiotics). These are environmental species, frequently found in soil, water, air, plants and insects [ 74 , 75 , 76 , 77 , 78 , 79 , 80 ]. Some of these species have been associated with infections in humans, namely immunocompromised individuals, but rarely [ 81 , 82 , 83 , 84 , 85 , 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…and P. vagans associated with S. aurata (excluding cases where these bacteria are used as probiotics). These are environmental species, frequently found in soil, water, air, plants and insects [ 74 , 75 , 76 , 77 , 78 , 79 , 80 ]. Some of these species have been associated with infections in humans, namely immunocompromised individuals, but rarely [ 81 , 82 , 83 , 84 , 85 , 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…Klebsiella michiganensis has appeared in parts of the world ( Ccorahua-Santo et al, 2017 ; King et al, 2021 ; Luo et al, 2022 ), there are highly homology and similarities in the molecular characteristics between K. michiganensis and K. pneumoniae . Some K. michiganensis strains have been found in plants or ecosystems ( Kang et al, 2020 ; Salgueiro et al, 2020 ; Liu, L. et al, 2021 ), but the majority have been found in patients ( Abed et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“… 2–4 In existing reports, there have been multiple genetic recombination and integration events of drug resistance genes through mobile genetic elements (MGEs) such as transposons and plasmids carried by K. michiganensis . 5–8 The existence and properties of plasmids make K. michiganensis isolates a serious threat, and it is of interest to conduct in-depth studies of the structure and function of the plasmids carried by K. michiganensis.…”
Section: Introductionmentioning
confidence: 99%